Coalbed methane adsorption capacity related to maceral compositions. Issue 1 (January 2020) - Liu, Langtao; Jin, Chao; Li, Lei; Xu, Chenyang; Sun, Pengfei; Meng, Zhaoxing; An, Lulu
Maceral compositions take a great role in coalbed methane adsorption. Two controversial viewpoints coexist on the effect of maceral compositions to coalbed methane adsorption. One is vitrinite has better adsorption capacity than inertinite and the other is inertinite has enhanced adsorption capacity than vitrinite. In order to clarify this issue, a series of coal samples were collected and highly purified vitrinite and inertinite concentrates were gained by heavy-fluid flotation and centrifugal separation. Isothermal adsorption experiments of methane were performed to these concentrates with equilibrium moisture and their ultimate adsorption volume were obtained finally. The results show that the adsorption capacity of vitrinite is weaker and the capacity of inertinite is stronger for low-rank coal. For high-rank coal, the adsorption capacity of vitrinite is stronger and the capacity of inertinite is weaker. Along with the increase of coal rank, the adsorption capacity of vitrinite rises gradually and the adsorption capacity of inertinite declines little by little. This result shows that the adsorption capacity of coal to methane not only relates to contents of vitrinite and inertinite, but also relates to metamorphic grade of the coal, because with the increase of metamorphism of coal, molecular structure, functional group and pore characteristic of vitrinite and inertinite change gradually, which results in tremendous changes in the adsorption capacity of coal.